Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Bank Umum Syari’ah Di Indonesia Tahun 2019-2023 - Nadia Rahmati; Fauzan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the influence of the board of commissioners, audit committee and board of directors on the financial performance of Islamic commercial banks in Indonesia in 2019-2023. This type of research is quantitative research. By taking data from the financial reports and annual reports of each Islamic commercial bank for 2019-2023. The sampling method used purposive sampling with a total of 54 from 2019-2023. This research uses multiple regression analysis. The results of this research show that the audit committee has an influence on financial performance. Meanwhile, the board of commissioners and board of directors have no effect on financial performance.